2017
DOI: 10.3174/ajnr.a5043
|View full text |Cite
|
Sign up to set email alerts
|

Structural Connectivity Analysis in Children with Segmental Callosal Agenesis

Abstract: Three malformative subtypes of segmental callosal agenesis were identified. Even the absence of a small callosal segment may impact global brain connectivity and modularity organization. The presence of ectopic callosal bundles may explain the greater interindividual variation in the connectomes of patients with segmental callosal agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In humans affected by CCA, remodeled cingulum bundles have been comprehensively described using DTI tractography ( 4 , 5 , 16 ). Among humans affected by CCA, compensatory neuroplasticity of the ipsilateral hemispheric axonal tracts is proposed as the mechanism responsible for remodeling of the cingulum and a variable degree of Probst bundle development is evident among patients ( 17 ). This aspect remains uncertain for canine CCA, as the present report is based on a single case; however, this presents an opportunity to prospectively screen for the presence and characteristics of Probst bundles using DTI.…”
Section: Discussionmentioning
confidence: 99%
“…In humans affected by CCA, remodeled cingulum bundles have been comprehensively described using DTI tractography ( 4 , 5 , 16 ). Among humans affected by CCA, compensatory neuroplasticity of the ipsilateral hemispheric axonal tracts is proposed as the mechanism responsible for remodeling of the cingulum and a variable degree of Probst bundle development is evident among patients ( 17 ). This aspect remains uncertain for canine CCA, as the present report is based on a single case; however, this presents an opportunity to prospectively screen for the presence and characteristics of Probst bundles using DTI.…”
Section: Discussionmentioning
confidence: 99%
“…Connectome and MRI analysis of individuals with segACC has shed light on the various paths axons take when they can not, or do not, properly decussate. Perhaps the most commonly observed surrogate pathway found in segACC would be the formation of Probst bundles - where axons run para-sagittally along the interhemispheric fissure instead of decussating midline [ 3 ]. Our case lacks the widely spaced frontal horns, and dilated trigones usually seen with the formation of Probst bundles.…”
Section: Discussionmentioning
confidence: 99%
“…This theory has fallen out of favor with support that callosal axons cross the midline through an area of secondary interhemispheric fusion, and that the cavum septum pellucidum is the portion of the interhemispheric fissure that becomes enclosed by the development of the surrounding corpus callosum [ 1 , 2 ]. Support for the latter theory has thus far been predicated upon: 1) Gross examination of anatomic specimens at various stages of development; 2) Magnetic resonance imaging (MRI), as in our case, reveals segmental agenesis between the genu and splenium, suggesting that the midline crossing bed of the developing corpus callosum (week 12 and 13) occurs after the anterior and hippocampal commissures cross (weeks 10 and 11 respectively) [ 1 , 2 ]; 3) Connectivity analysis with diffusion tensor imaging and tractography has revealed that cingulate cortex axonal projections from multiple distinct loci decussate the commissural plate, giving rise to the anterior and hippocampal commissures, which later fuse to form the corpus callosum [ 1 , 3 ]. Although the corpus callosum appears to grow in a rosto-caudal fashion, the commissure actually grows in conjunction with the hemispheres, with the genu developing prenatally, and the splenium mostly growing postnatally [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Callosal malformations vary extensively in their presentation, from hypoplasic (reduced midsagittal CC area) and partial (usually with a rostral CC remnant in humans and caudal in mice) formations to complete agenesis ( Tovar-Moll et al, 2006 ). Regardless of the degree of callosal malformations, reorganization of the CCD brain can generate new aberrant white matter fiber bundles ( Probst, 1901 ; Tovar-Moll et al, 2006 ; Paul et al, 2007 ; Kasprian et al, 2013 ; Severino et al, 2017 ; Edwards et al, 2020 ; Szczupak et al, 2020a ), leading to widespread structural ( Owen et al, 2013b ; Jakab et al, 2015 ; Siffredi et al, 2020 ; Szczupak et al, 2021b ), and functional ( Owen et al, 2013a ; Tovar-Moll et al, 2014 ; Lazarev et al, 2016 ; Monteiro et al, 2019 ; Szczupak et al, 2020b , 2021b ) changes affecting the entire brain. For example, hypoplasic CCD subjects and mouse models have an atypical structural brain connectivity profile that is substantially different from that of healthy subjects ( Owen et al, 2013b ; Edwards et al, 2020 ; Szczupak et al, 2020a , 2021b ; Siffredi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%